Konsistensi Kompilasi Hukum Islam dengan Undang-Undang Nomor 1 Tahun 1974 Pasal 43 Mengenai Hak Waris Anak Perkawinan Siri - Komarudin; M. Syahnan Harahap (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
One of the impacts of unregistered marriage lies in the status of children. Children of unregistered marriages according to Indonesian positive law have the same status as illegitimate children, where illegitimate children only have a civil relationship with their mother, and in the birth certificate they are only listed in the mother's name. In fact, later it will be difficult for the child to be in the position of heir when he demands what is his right, apart from that he has no right to a living, education and inheritance from his father. The title of this research is Consistency of the Compilation of Islamic Law with Law Number 1 of 1974 Article 43 Concerning the Inheritance Rights of Children of Siri Marriages. Problem formulation: How are the inheritance rights of children from unregistered marriages regulated based on the compilation of Islamic law? What is the consistency of Law Number 1 of 1974 Article 43 with the Compilation of Islamic Law regarding the inheritance rights of children of unregistered marriages? The research was conducted using a normative juridical approach. The data used is primary, secondary and tertiary data. Data analysis was carried out qualitatively and based on the results of the analysis, conclusions were then drawn using a deductive approach. The conclusion of this research is that the Marriage Law and the Compilation of Islamic Law have similarities regarding the legal position of children in unregistered marriages. Based on these provisions, children of unregistered marriages do not fulfill the elements of being legitimate children according to Article 42 of the Marriage Law because in order to fulfill the elements of a valid marriage according to the Marriage Law, it must be officially registered. So it can be concluded that children of unregistered marriages based on the Marriage Law and KHI are children outside of marriage. So the legal consequences according to both are the same, namely that children of unregistered marriages do not have inheritance rights from their father because they are considered to only have a civil relationship with their mother.